Clinical and predictive value of simplified creatinine index used as muscle mass surrogate in end-stage kidney disease haemodialysis patients—results from the international MONitoring Dialysis Outcome initiative. Issue 12 (24th August 2020) - Canaud, Bernard; Ye, Xiaoling; Usvyat, Len; Kooman, Jeroen; van der Sande, Frank; Raimann, Jochen; Wang, Yuedong; Kotanko, Peter
Abstract: Background: Protein-energy wasting, muscle mass (MM) loss and sarcopenia are highly prevalent and associated with poor outcome in haemodialysis (HD) patients. Monitoring of MM and/or muscle metabolism in HD patients is of paramount importance for timely detection of muscle loss and to intervene adequately. In this study we assessed the reliability and reproducibility of a simplified creatinine index (SCI) as a surrogate marker of MM and explored its predictive value on outcome. Method: We included all in-centre HD patients from 16 European countries with at least one SCI. The baseline period was defined as 30 days before and after the first multifrequency bioimpedance spectroscopy measurement; the subsequent 7 years constituted the follow-up. SCI was calculated by the Canaud equation. Multivariate Cox proportional hazards models were applied to assess the association of SCI with all-cause mortality. Using backward analysis, we explored the trends of SCI before death. Bland–Altman analysis was performed to analyse the agreement between estimated and measured MM. Results: We included 23 495 HD patients; 3662 were incident. Females and older patients have lower baseline SCI. Higher SCI was associated with a lower risk of mortality [hazard ratio 0.81 (95% confidence interval 0.79–0.82)]. SCI decline accelerated ∼5–7 months before death. Lean tissue index (LTI) estimated by SCI was correlated with measured LTI in both sexes (males: R 2 = 0.94; females: R 2 = 0.92; both P < 0.001). Bland–Altman analysis showed that measured LTI was 4.71 kg/m 2 (±2 SD: −12.54–3.12) lower than estimated LTI. Conclusion: SCI is a simple, easily obtainable and clinically relevant surrogate marker of MM in HD patients.